2017
DOI: 10.1177/8755122517704212
|View full text |Cite
|
Sign up to set email alerts
|

Digital Medicine: Innovative Drug-Device Combination as New Measure of Medication Adherence

Abstract: In September 2015, the Food and Drug Administration accepted the first digital medicine new drug application for a drugdevice combination of Otsuka's Abilify ® (aripiprazole) and an ingestible sensor embedded in the tablet that digitally records ingestion. When this digital medicine is taken, it sends a signal to a patch worn by the patient. The information is recorded, time-stamped, and relayed to any Bluetooth-enabled device and, with patients' consent, to their physicians and/or their caregivers. An encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The demonstration of acceptable PK of several commonly used ARVs coencapsulated with an ingestible sensor creates a digital medication that can be used to measure and track a patients' ARV adherence in real-time. 24,26,42 The findings from this study also provide some confidence that for those coencapsulated ARVs where PK characteristics did not meet our definition of no difference (e.g., EVG and RPV), the magnitude of differences in PK characteristics were unlikely to be clinically significant; our findings reinforce the recommendations that EVG and RPV must be administered with food. Collectively, the data from this study allow initiation of a planned randomized controlled trial to assess the feasibility, acceptability, and effectiveness of the ingestible sensor to investigate ARV adherence.…”
Section: Fig 3 Mean Concentration-time Curves For Bictegravir (Bic) In Biktarvysupporting
confidence: 70%
“…The demonstration of acceptable PK of several commonly used ARVs coencapsulated with an ingestible sensor creates a digital medication that can be used to measure and track a patients' ARV adherence in real-time. 24,26,42 The findings from this study also provide some confidence that for those coencapsulated ARVs where PK characteristics did not meet our definition of no difference (e.g., EVG and RPV), the magnitude of differences in PK characteristics were unlikely to be clinically significant; our findings reinforce the recommendations that EVG and RPV must be administered with food. Collectively, the data from this study allow initiation of a planned randomized controlled trial to assess the feasibility, acceptability, and effectiveness of the ingestible sensor to investigate ARV adherence.…”
Section: Fig 3 Mean Concentration-time Curves For Bictegravir (Bic) In Biktarvysupporting
confidence: 70%
“…Ingestion data are displayed on this interface, and are accessible to patients via a mobile application, and to researchers and clinicians via an online system (14). By capturing objective medication ingestion data in real time, DPS present a novel method of adherence measurement that can promptly identify episodes and patterns of suboptimal adherence, and that allow for notification to a patient's care team prior to the onset of persistent nonadherence (14,(20)(21)(22).…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%
“…This technology has been used in those treated for a variety of disease states, including hypertension, mental health conditions, tuberculosis, and organ transplantation. [9][10][11][12][13] Studies have reported at least 95% detection sensitivity and 99.7% specificity. 8,12 However, this device has not yet been tested for ARV therapy use in HIV-infected individuals.…”
Section: Real-time Adherence Monitoring With Ingestion Sensormentioning
confidence: 99%
“…A short message system can be programmed in response to the receipt (or not) of the ingestion signal, for example, a reinforcing message if a dose is taken and a reminder after a scheduled dose is missed. This technology has been used in those treated for a variety of disease states, including hypertension, mental health conditions, tuberculosis, and organ transplantation . Studies have reported at least 95% detection sensitivity and 99.7% specificity .…”
mentioning
confidence: 99%